(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The implementation proposal to create an RFID control prototype to optimize the entry of teachers and monitoring that measures the temperature and brightness levels in the classroom in the Industrial Engineering Faculty of the University of Guayaquil to achieve a Smart Campus. In this project, the Xbee wireless communication system was used to communicate the sensors with the central unit. In addition, this project proposes the resolution to the existing problems that burden the university community to improve the work environment and increase student motivation and optimizing the entry of teachers to the classrooms. Three research methods were used: bibliographic, descriptive and experimental. Reliability results of 95% of the temperature sensors were obtained. In addition, the brightness sensor nodes were verified to have an effectiveness rate of 99%. Finally, it was verified that the sensor nodes transmitted the data to the central node without any loss of data and the transmission times were efficient. Finally, it is concluded that the field tests carried out determined that it is a low cost, low energy consumption and easy to install system.